Political Philosophies in Moral Conflict - S.Wenz Peter (MC Graw Hill, 2007)
Political Philosophies in Moral Conflict presents the theories and issues of political philosophy as tools for understanding and expressing the various views of the role of the state in people's lives. Students will explore the impact of classic and contemporary philosophical theories as they affect the political structure of lives today through a variety of current, controversial debates such as racial profiling, drug legalization, pollution control and physician-assisted suicide. Cases such as school vouchers, Microsoft's trade restraint, polygamy, and abortion offer a way to demonstrate the practical impact of competing political philosophies.